Linezolid and Its Immunomodulatory Effect: In Vitro and In Vivo Evidence - Wang, Jin; Xia, Lei; Wang, Rui; Cai, Yun (Frontiers in Pharmacology, 2019)
Recently, effects of some antibacterial agents on various aspects of the immune response to infection have been explored in addition to their bactericidal effects. Linezolid (LZD), a synthetic oxazolidinone class of antibacterial agent, exhibits activity against a broad range of Gram-positive bacteria. This review summarized the effects of LZD on the immune response and new approaches that can exploit this interaction for the treatment of bacterial infections. In vitro and pre-clinical evidence demonstrates that LZD suppresses the phagocytic ability, cytokine synthesis and secretion of immune cells as well as the expressions of immune-related genes at the mRNA level under the stimulation of endotoxin or pathogens. Immunomodulatory effects of LZD can not only reduce the inflammatory damage induced by exaggerated or prolonged release of pro-inflammatory cytokines during infections, but also be applied to alleviate the symptoms of noninfectious inflammatory conditions. Further research is necessary to explore the molecular mechanisms and confirm these findings in clinical practice.